Taxpayer Compliance Based on the Theory of Planned Behavior in Individual Taxpayers in the City of Padang - Andre Agassy; Aries Tanno (E-Jurnal Akuntansi, 2024)
This study aims to find out the compliance behavior of individuals in Padang city where higher tax receipts are reversed compared to the level of compliance existing by conducting research using the Theory of Planned Behavior. This theory covers attitudes, subjective norms, controlled behavior, intent, and tax compliance. The survey sample consisted of 30 respondents with compulsory personal tax criteria with entrepreneurial and freelance criteria selected using the convenience sampling approach. This research uses primary data derived from the dissemination of the questionnaire. The Warp-PLS utility is used to assist in data analysis for the tests carried out in this study. The findings of this study include: (1) controls of behavior that are perceived to be factors influencing the obedient intentions and compliance with the tax obligations of individuals, (2) subjective attitudes and norms cannot be empirically proven regarding the influence on the obedience intentions on taxpayers of individuals.